(untitled) (Bangladesh Journal of Medical Science, 2021)
Ectopic salivary gland tissue (ESGT) is salivary tissue located outside the major, minor and accessory salivary glands. Neoplasms rarely arise from ESGT, let alone carcinoma expleomorphic adenoma (CEPA) which is a malignant tumour that arises from the epithelial component of pleomorphic adenoma. It usually occurs in the parotid gland and in lesser instances, from submandibular gland or minor salivary glands. Herein, we report a rare case of CEPA in right supraclavicular ESGT of a 67-year-old lady.She underwent complete surgical excision of the mass and is free from any recurrence to date. Brief review of pathogenesis, clinical features and treatment of ectopic CEPA are discussed. A thorough review of the English literature reveals that our patient may be the second case of ectopic CEPA in the neck region ever reported to date. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.658-661